Respuesta :

Answer:

Ay=3 over 2 or y=-2 over 3

Step-by-step explanation:

the quadratic formula: y={-b±√(b²-4ac)}/2a

In the equation 6y²-5y-6= 0, a=6, b=-5, c= -6

Substituting for the values in the formula we get:

{-(-5)±√[(-5²)-4(6)(-6)}/2(6)

{5±√169}12

={5±13}/12

(5+13)/12=3/2 or (5-13)/12= -2/3

Answer:

[tex]y=\frac{3}{2}[/tex] or [tex]y=-\frac{2}{3}[/tex]

Step-by-step explanation:

We have the expression

[tex]6y^2-5y-6 = 0[/tex]

For an equation of the form [tex]ay^2 +by +c[/tex]  the quadratic formula is

[tex]y=\frac{-b \± \sqrt{b^2 -4ac}}{2a}[/tex]

In this case

[tex]a = 6\\b= -5\\c =-6[/tex]

[tex]y=\frac{-(-5) \± \sqrt{(-5)^2 -4(6)(-6)}}{2(6)}[/tex]

[tex]y_1=\frac{3}{2}[/tex]

[tex]y_2=-\frac{2}{3}[/tex]